An Applied Analysis: Master and Doctoral Students of Healthcare Management and Their Internet Usage for Scientific Research, - Korkmaz, M., Kılıç, B., Yücel, A. S., Aksoy, M., Çatıkkaş, F., (My University, 2014)
In this study it is aimed to identify the academic competency of master and doctorate students in the field of healthcare management and to determine the level of research conducted in the academic field. The target population of the study is Istanbul, Sakarya and Ankara provinces and sampling is made up of master and doctorate students attending to state and private universities in these provinces. Five-point Likert Scale and a questionnaire made up of two sections are used in this study. In total 258 individuals (N=258) participated in the study. 0.920 was obtained as the Cronbach Alfa coefficient. Within the scope of analysis, Kolmogorov Smirnov, Mann Whitney U, Chi-Square and Kruskal Wallis H tests were used. As a result of the study, it was found out that internet usage levels of the master and doctorate students studying in the field of healthcare management were very low in terms of academic research and their use was not effective.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Internet; student; science; research; technique; academic; health; management